SECRETS OF LONG LIFE - Qo’ldosheva Mo’tabar Muhtarovna (TADQIQOTLAR, 2025)
The bold letters in the heading on the email in my inbox read, “Harvard research suggests meaningful relationships are a prescription for better emotional, mental, and physical health and possibly more critical to longevity than exercise or diet.”